Comparison of Baska mask and I-gel with endotracheal tube in laparoscopic cholecystectomy: A randomized controlled study - Avijit Gain; Suchismita Mallick; Sujata Ghosh; Sarbari Swaika; Uday Sankar Mandal; Arpita Choudhury (Asian Journal of Medical Sciences, 2024)
Background: Supraglottic airway devices are frequently used instead of endotracheal intubation in laparoscopic surgeries. Two such devices, I-gel (IG) and Baska mask (BM), have been compared with respect to their sealing properties and leak fraction (LF) in comparison to the endotracheal tube. Aims and Objectives: The aim of the present study is to compare the performance of IG and BM with endotracheal tube in patients undergoing laparoscopic cholecystectomy under general anesthesia. Materials and Methods: In this randomized trial, 84 patients scheduled for laparoscopic cholecystectomy under general anesthesia were randomized to group (endotracheal tube [ETT], n=28), group BM (BM, n=28), or group IG (IG, n=28). All the patients received standard general anesthesia and the airway was maintained with either of three devices. The primary outcomes were the difference in the LF and airway sealing pressure (ASP) at different time points before and after pneumoperitoneum. Secondary outcomes were insertion-time, number of insertion attempts, and gastric insufflations. Heart rate and blood pressure were recorded. Complications such as sore throat, coughing, laryngospasm, blood staining of the device, and aspiration were noted. Results: P-values of LF of the three groups at time points T- after insertion (Ti), T-after pneumoperitoneum (Tp), and T- after peritoneal deflation (Tr) were 0.000 each and P-values of ASP at those time points were 0.000 each, respectively. Insertion time was significantly less for IG than ET (P<0.001). Heart rate and blood pressure showed P-values at Ti and Tp (P=0.004 and 0.000). Conclusion: It was concluded that IG or BM can maintain an airway with adequate seal and were not associated with any incidence of aspiration or laryngospasm. IG placement was found to be easier whereas the ease of ventilation was noted with BM.